Preoperative methylprednisolone increases plasma Pentraxin 3 early after total knee arthroplasty: a randomized, double-blind, placebo-controlled trial. (9th November 2017) - Lindberg-Larsen, V; Kehlet, H; Pilely, K; Bagger, J; Rovsing, M L; Garred, P
Summary: Preoperative glucocorticoid administration reduces the systemic inflammatory response. Pentraxin 3 (PTX3) is a novel inflammatory marker belonging to the humoral arm of innate immunity exerting a potentially protective host response. This study evaluated PTX3 and other complement marker changes after preoperative methylprednisolone (MP) early after total knee arthroplasty (TKA). Seventy patients were randomized (1 : 1) to preoperative intravenous (i.v.) MP 125 mg (group MP) or isotonic saline i.v. (group C). The outcomes included change in plasma PTX3, mannose-binding lectin (MBL), ficolins (ficolin-1, −2 and −3), complement components (C4 and C3), terminal complement complex (TCC) and C-reactive protein (CRP) concentrations. Blood samples were analysed at baseline and 2, 6, 24 and 48 h after surgery with complete sampling from 63 patients for analyses. MP resulted in an increase in circulating PTX3 compared to saline from baseline to 24 h postoperatively ( P < 0·001), while MP reduced the systemic inflammatory response (CRP) 24 and 48 h postoperatively ( P < 0·001). However, the small postoperative changes in MBL, ficolin-1, −2 and −3, C4, C3 and TCC concentrations did not differ between groups ( P > 0·05). In conclusion, preoperative MP 125 mg increased circulating PTX3 and reduced the general inflammatory response (CRP) early after TKA, but did not affect other complement markers. Graphical Abstract: